2018
DOI: 10.1002/ijgo.12566
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for successful cervical ripening using a double‐balloon catheter after previous cesarean delivery

Abstract: Several factors were found to predict successful cervical ripening using DBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
9
0
3
Order By: Relevance
“…For example, cervical ripening is regularly used in women with one previous cesarean delivery in France [26][27][28]. In our team, women with one previous cesarean delivery are not contraindicated to mechanical device and its practice is usual and well framed [29]. Other strengths also include performance of individual and prospective collection of data throughout the study period by the same physician and using a standardized protocol according to Bishop score (systematic cervical ripening for IOL with an unfavorable cervix (Bishop score <6), repeating cervical ripening until Bishop score will be above 6).…”
Section: Discussionmentioning
confidence: 98%
“…For example, cervical ripening is regularly used in women with one previous cesarean delivery in France [26][27][28]. In our team, women with one previous cesarean delivery are not contraindicated to mechanical device and its practice is usual and well framed [29]. Other strengths also include performance of individual and prospective collection of data throughout the study period by the same physician and using a standardized protocol according to Bishop score (systematic cervical ripening for IOL with an unfavorable cervix (Bishop score <6), repeating cervical ripening until Bishop score will be above 6).…”
Section: Discussionmentioning
confidence: 98%
“…With the increasing rate of multiparous women in China, birth defects are a challenging issue. Women at very advanced maternal age (≥ 43 years) have a higher risk of preeclampsia, intrauterine growth retardation, stillbirth, and placental abruption than the younger counterparts [14]. Zhang X et al [15] analyzed 1,260,684 births from the surveillance system in Zhejiang province, China, and found that the rate of birth defects during 2013, 2015, and 2017 was 245.95, 264.86, and 304.36 per 10,000 births, respectively, and there was age-related anomalies after the release of China's new two-child policy.…”
Section: Discussionmentioning
confidence: 99%
“…[1921] The ripening of cervical is difficult in some cases by oral mifepristone or oral mifepristone combined with extra-amniotic administration of ethacridine lactate. Some studies [6,2223] have specifically reported on the use of DBC for cervical ripening among women with previous cesarean and an unfavorable cervix. The results show that DBC is useful and safe, which results an increase in the Bishop score of patients’ cervix but no increased risk of perinatal adverse events, such as cesarean delivery rate, neonatal outcome, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…DBC [6,12] is usually used as per the manufacturer's instructions (Cervical Ripening Balloon; Cook OB/GYN, Spencer, IN, USA). It involves 2 balloons.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation